The utility of thromboelastometry in prophylactic platelet transfusion for hematological malignancies. Issue 1 (August 2015) - Akay, Olga Meltem; Goren Sahin, Deniz; Andic, Neslihan; Gunduz, Eren; Karagulle, Mustafa; Colak, Ertugrul; Gulbas, Zafer
Abstract There is still debate on how platelet transfusions should be used to prevent severe bleeding. The aim of our study is to assess the clinical efficacy of thromboelastometry in reducing number of prophylactic platelet transfusions in patients with hematological malignancies. One hundred hematological malignancy patients were included in the study. Six units random donor platelets (RDPs) was given to the first group, three units RDPs was given to the second group, one unit single donor platelets (SDPs) was given to the third group, and 1/2 unit SDPs was given to the fourth group. Before and 15 minutes after transfusion, rotation thromboelastometry (ROTEM) was performed (Pentapharm GmbH, Munich, Germany). ROTEM® parameters did not show any statistical difference between 'low dose' and 'high dose' random or single donor platelet transfusions. Therefore, low dose platelet transfusion can be considered because of its reduced adverse transfusion reactions and economic burden.